Non-Infectious Scleritis and Systemic Collagen Vascular Disease Association - Sutasinee Boonsopon; Pitipol Choopong; Wisakorn Wongwijitsook; Wanchana Sopitviriyaporn; Nattaporn Tesavibul (Siriraj Medical Journal, 2020)
Objective: To evaluate scleritis type in association with a systemic collagen vascular disease and the clinical characteristics of patients presenting with non-infectious scleritis. Methods: A retrospective chart review of 95 patients who presented with non-infectious scleritis was conducted. A comparison of the clinical differences between patients who had an associated systemic collagen vascular disease and idiopathic scleritis was performed. Results: Of the 95 patients (123 eyes), 72.6% was female with mean age of 47 years. Diffuse anterior scleritis was the most predominant type (57.9%). The first and the second most frequent complications were anterior uveitis and scleral thinning. Almost twenty percent of the patients had a systemic collagen vascular disease involvement; rheumatoid arthritis and non-specific anti-neutrophil cytoplasmic antibodies-related scleritis were the two most common at 4.2% each. Most of patients who had a concurrent systemic collagen vascular disease presented with diffuse anterior scleritis, and it was statistically significant compared with the idiopathic group. The presence of scleral thinning during follow-up periods was a statistically significant difference between the groups with and without systemic collagen vascular disease. Conclusion: Diffuse anterior scleritis was the most common scleritis found. The association between diffuse anterior scleritis and a systemic collagen vascular disease was higher than those for nodular anterior scleritis and posterior scleritis. The possibility of a systemic collagen vascular disease association and the potential for devastating sight- and life-threatening complications need to be considered for any patient who has scleritis.